The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Sustainable probiotic production via AI: medium optimization and metabolic mechanisms in Bifidobacterium animalis ssp. lactis BB-12 using agricultural waste - Huijuan Zhang; Ruifang Feng; Ning Ding; Tianzhuo Huang; Hui Hong; Yongkang Luo; Sam K. C. Chang; Yan Zhang; Yuqing Tan (Critical Reviews in Food Science and Nutrition, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Genomic prediction accuracy in Korean Holstein population: A comprehensive study of milk production traits - Md Azizul Haque; You-Sam Kim; Chang-Gwon Dang; Yun-Mi Lee; Jong-Joo Kim (The Veterinary Journal, 2025)

Chia seed mucilage biosorbent synergism with hydrophobic iron (III)-natural phenolic nanoparticles for dispersive solid-phase extraction of tetracycline residues in milk and honey samples before HPLC analysis - Nongnapas Nakhonchai; Kraingkrai Ponhong; Jonathan V. Sweedler; Chang Young Lee; Sam-ang Supharoek (Food Chemistry, 2025)

Hwangkeumjakyak-tang protects against hepatocyte damage via oxidative stress inhibition and affects the altered gut microbiome pattern in acetaminophen-induced liver injury - Sam Seok Cho; So Hi Kang; Jeon Kyung Kim; Yu Bin Lee; Hong Seok Son; Jae Min Kim; Chang Su Na; Ji Hye Yang (Advances in Traditional Medicine, 2025)
Hwangkeumjakyak-tang (HJT), a Korean traditional herbal medicine, is known to clear phlegm, relieve congestion, and reduce inflammation. However, there is a lack of research on the efficacy of HJT in other diseases. The present study aimed to investigate whether HJT could protect against liver injury. We first examined the effects of HIT in vitro by assessing its toxicity and the phosphorylation and nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) in human HepG2 cells. Additionally, we investigated whether HJT inhibited oxidative stress by measuring reactive oxygen species (ROS) production and intracellular levels of reduced glutathione (GSH). We further assessed the effects of HJT in vivo by analyzing liver damage parameters using an acetaminophen (APAP)-induced liver damage mouse model. Treatment with HJT significantly reduced the elevated serum levels of ALT and AST and the cytokine release induced by APAP injection. Furthermore, we verified that treatment with HJT suppressed APAP-induced ROS production and GSH depletion in the mouse liver, suggesting that HJT inhibited APAP-induced liver injury by blocking oxidative stress in vivo. To identify the potential relationship between the liver and intestine for liver disease therapy, we also performed 16S rRNA amplicon sequencing to analyze the gut microbiome and confirmed that HJT regulated APAP-induced changes in the gut microbiome pattern. In conclusion, HJT, a Nrf2 activation inducer, exhibits a cytoprotective effect on APAP-induced liver injury and can regulate the gut microbiome altered by the administration of APAP.

Machine learning-guided anti-photoaging peptides from Chinese giant salamander skin: Efficient preparation and mechanistic insights - Yongjie Zhou; Huijuan Zhang; Chunyue Zhao; Zixin Fu; Yuting Wang; Sam K.C. Chang; Yan Zhang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Food Chemistry, 2025)

Resveratrol-myosin interaction: A novel strategy for mitigating quality deterioration in frozen sturgeon surimi - Jiayi Zhou; Lu Tong; Yongjie Zhou; Yongkang Luo; Hui Hong; Sam K.C. Chang; Yan Zhang; Yuqing Tan (Food Chemistry, 2025)

Bi-stage learning differential evolution for multimodal optimization problems - Chang-Long Wang; Zi-Jia Wang; Yi-Biao Huang; Dan-Ting Duan; Zhi-Hui Zhan; Sam Kwong; Jun Zhang (Swarm and Evolutionary Computation, 2025)

Silver carp by-product hydrolysate: A promising mucin substitute for stimulating Akkermansia muciniphila growth and metabolic activity - Huijuan Zhang; Rui Zhang; Shengjun Chen; Ruifang Feng; Sam K.C. Chang; Yongkang Luo; Hui Hong; Yuqing Tan (Food Bioscience, 2025)

Unveiling a new chapter for collagen peptides: Comprehensive insights into oral bioavailability and the enhancement via encapsulation systems - Yongjie Zhou; Yanfei Jiang; Yan Zhang; Wallace Yokoyama; Jianping Wu; Sam K.C. Chang; Hui Hong; Yongkang Luo; Bo Li; Yuqing Tan (Trends in Food Science & Technology, 2025)

Association between intraspecific variability and penicillin production in industrial strain, Penicillium chrysogenum revealed by RAPD and SRAP markers - Yu Jong Ri; Chang Ho Ri; Un Hyang Ho; Sam Rang Song; Il Sim Pak; Tae Ryong Ri; Yong Jo Kim; Jun Song Ri (World Journal of Microbiology and Biotechnology, 2025)

Sex-specific trade-off under marine heat wave and food limitation: Insights from bioenergetic and intestinal microbiome in mussels - Yueyong Shang; Xueqing Chang; Fahim Ullah Khan; Sam Dupont; Menghong Hu; Youji Wang (Aquaculture, 2025)

Macrofouling remediation strategies for water intakes of desalination and other industrial plants – A review - Ying Shi Chang; Catherine J. Munro; Luca Fortunato; Abdulla AlAli; Christian Marciulescu; Sam Lindsey Harvey; Johannes Vrouwenvelder; Hassan Arafat; Ludovic F. Dumée (Desalination, 2024)

Genetic Diversity and Population Structure in Chestnut (Castanea spp.) Varieties Revealed by RAPD and SRAP Markers - Un-Hyang Ho; Chang-Hyok Kim; Il-Jin Kim; Yong-Il Chon; Hye-Song Kim; Sam-Rang Song; Song-Hyok Pak (Agricultural Research, 2024)

Plastein reaction enhances the emulsifying and rheological properties of silver carp hydrolysates in oil-in-water emulsions - Yongjie Zhou; Chunsong Feng; Hui Hong; Yongkang Luo; Sam K.C. Chang; Yuqing Tan (Food Hydrocolloids, 2024)

Utilizing fish waste as a sustainable nitrogen source for enhancing growth and metabolism regulation in Bifidobacterium animalis ssp. lactis BB-12 - Huijuan Zhang; Yan Zhang; Sam K.C. Chang; Yongkang Luo; Hui Hong; Yuqing Tan (Journal of Cleaner Production, 2024)

Characterization and Applications of Permeabilized Hepatocytes in Drug Discovery - Sam Zhang; Christine C. Orozco; Lloyd Wei Tat Tang; Jillian Racich; Anthony A. Carlo; George Chang; David Tess; Christopher Keefer; Li Di (The AAPS Journal, 2024)

Development of a qPCR detection approach for pathogenic Burkholderia cenocepacia associated with fresh vegetables - Aixin Liu; Kate Phillips; Jiayuan Jia; Peng Deng; Dunhua Zhang; Sam Chang; Shi-En Lu (Food Microbiology, 2023)

Ocean acidification increases inorganic carbon over organic carbon in shrimp's exoskeleton - Veran Weerathunga; Chin-Chang Hung; Sam Dupont; Hsueh-Han Hsieh; Nathangi Piyawardhana; Fei-Ling Yuan; Kai-Jung Kao; Kuei-Chen Huang; Wei-Jen Huang (Marine Pollution Bulletin, 2023)

Molecular mechanisms of coronary microvascular endothelial dysfunction in diabetes mellitus: focus on mitochondrial quality surveillance - Danan Sun; Jin Wang; Sam Toan; David Muid; Ruibing Li; Xing Chang; Hao Zhou (Angiogenesis, 2022)

Impacts of pH on the Fitness and Immune System of Pacific White Shrimp - Veran Weerathunga; Wei-Jen Huang; Sam Dupont; Hsueh-Han Hsieh; Nathangi Piyawardhana; Fei-Ling Yuan; Jhe-Syuan Liao; Chia-Yu Lai; Wei-Ming Chen; Chin-Chang Hung (Frontiers in Marine Science, 2021)
The atmospheric partial pressure of CO 2 ( p CO 2 ) has been increasing dramatically since the beginning of the industrial revolution and about 30% of the CO 2 produced by anthropogenic activities was absorbed by the ocean. This led to a perturbation of the seawater carbonate chemistry resulting in a decrease of the average surface ocean pH by 0.1 and termed ocean acidification (OA). Projections suggest that p CO 2 may reach 900 μatm by the end of the twenty-first century lowering the average pH of the surface ocean by 0.4 units. The negative impacts of OA on many species of marine invertebrates such as mollusks, echinoderms, and crustaceans are well documented. However, less attention has been paid to the impacts of low pH on fitness and immune system in crustaceans. Here, we exposed Pacific white shrimps to 3 different pHs (nominal pH 8.0, 7.9, and 7.6) over a 100-days experiment. We found that, even though there were no significant effects on fitness parameters (survival, growth and allometries between length and weight), some immune markers were modified under low pH. A significant decrease in total hemocyte count and phenoloxidase activity was observed in shrimps exposed to pH 7.6 as compared to pH 8.0; and phagocytosis rate significantly decreased with decreasing pH. A significant increase in superoxide production was also observed at pH 7.6 as compared to pH 8.0. All these results suggest that a 100-days exposure to pH 7.6 did not have a direct effect on fitness but lead to a modulation of the immune response.

Gonadal antioxidant responses to seawater acidification and hypoxia in the marine mussel Mytilus coruscus - Guangen Xu; Hui Kong; Xueqing Chang; Sam Dupont; Hui Chen; Yuewen Deng; Menghong Hu; Youji Wang (Environmental Science and Pollution Research, 2021)

Quantifying the effect of uncertainty in input parameters in a simplified bidomain model of partial thickness ischaemia - Barbara M. Johnston; Sam Coveney; Eugene T. Y. Chang; Peter R. Johnston; Richard H. Clayton (Medical & Biological Engineering & Computing, 2018)

14-3-3β Depletion Drives a Senescence Program in Glioblastoma Cells Through the ERK/SKP2/p27 Pathway - Sung Bin Seo; Je-Jung Lee; Hye Hyeon Yun; Chang-Nim Im; Yong-Sam Kim; Jeong-Heon Ko; Jeong-Hwa Lee (Molecular Neurobiology, 2018)

Depletion of BIS sensitizes A549 cells to treatment with cisplatin - Mei Nu Cui; Hye-Hyeon Yun; Nan Ee Lee; Hye Yun Kim; Chang-Nim Im; Yong-Sam Kim; Jeong-Hwa Lee (Molecular & Cellular Toxicology, 2016)

Fabrication of 3D alginate scaffold with interconnected pores using wire-network molding technique - Se-Hwan Lee; A. Ra Jo; Ghi Pyoung Choi; Chang Hee Woo; Seung Jae Lee; Beom-Su Kim; Hyung-Keun You; Young-Sam Cho (Tissue Engineering and Regenerative Medicine, 2013)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Inhibitory effect of Jeju endemic seaweeds on the production of pro-inflammatory mediators in mouse macrophage cell line RAW 264.7 - Eun-Jin Yang; Ji-Young Moon; Min-Jin Kim; Dong Sam Kim; Chan-Shick Kim; Wook Jae Lee; Nam Ho Lee; Chang-Gu Hyun (Journal of Zhejiang University-SCIENCE B, 2010)

Ecklonia stolonifera inhibits lipopolysaccharide-induced production of nitric oxide, prostaglandin E2, and proinflammatory cytokines in RAW264.7 macrophages - Eun-Jin Yang; Young-Min Ham; Dong Sam Kim; Ji-Young Kim; Jung Pyo Hong; Min-Jin Kim; Ji-Young Moon; Wook Jae Lee; Nam Ho Lee; Chang-Gu Hyun (Biologia, 2010)

Antibacterial activity of novel naphthoquiones derivatives - Yongseog Chung; Ren shu Quan; Hyeon Mo Chang; Soo Han Kwon; Soon-Ja Kim; Young-Sam Im; Kyeong Seob Shin; Kyung-Do Park; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2009)

ITS2 ribosomal DNA sequence variation of the bumblebee,Bombus ardens (hymenoptera: Apidae) - Hyung Keun Oh; Hyung Joo Yoon; Min Jee Kim; Hyung Uk Jeong; Seong Ryul Kim; Jae Sam Hwang; Chang Hwan Bae; Iksoo Kim (Genes & Genomics, 2009)

Voltammetric Bioassay of Caffeine using Sensor Implant - Suw Young Ly; Chang Hyun Lee; Young Sam Jung (NeuroMolecular Medicine, 2009)

Prostate volume modifies the association between obesity and prostate cancer or high-grade prostatic intraepithelial neoplasia - Jay H. Fowke; Saundra S. Motley; Marcia Wills; Michael S. Cookson; Raoul S. Concepcion; Charles W. Eckstein; Sam S. Chang; Joseph A. Smith (Cancer Causes & Control, 2007)

Effect of l-carnitine supplementation and aerobic training on FABPc content and β-HAD activity in human skeletal muscle - Jang Kyu Lee; Jong Sam Lee; Hyon Park; Youn-Soo Cha; Chung Su Yoon; Chang Keun Kim (European Journal of Applied Physiology, 2006)

Fruit ripening-related expression of a gene encoding group 5 late embryogenesis abundant protein inCitrus - Oh-Sung Jeon; Chan-Shick Kim; Sam-Pin Lee; Sung Ku Kang; Chang-Myung Kim; Bong-Gyoon Kang; Yoonkang Hur; In-Jung Kim (Journal of Plant Biology, 2006)

Enhancement of xylitol productivity and yield using a xylitol dehydrogenase gene-disrupted mutant of Candida tropicalis under fully aerobic conditions - Byoung Sam Ko; Chang Hoon Rhee; Jung Hoe Kim (Biotechnology Letters, 2006)

Utility of Ten-Day Climate Model Ensemble Simulations for Water Resources Applications in Korean Watersheds - Konstantine P. Georgakakos; Deg-Hyo Bae; Chang-Sam Jeong (Water Resources Management, 2005)

A Cuticle Protein Gene from the Japanese Oak Silkmoth, Antheraea yamamai: Gene Structure and mRNA Expression - Bo Yeon Kim; Nam Sook Park; Byung Rae Jin; Bong Hee Lee; Su Il Seong; Jae Sam Hwang; Jong Su Chang; Sang Mong Lee (Biotechnology Letters, 2005)

Effect of exercise training on muscle glucose transporter 4 protein and intramuscular lipid content in elderly men with impaired glucose tolerance - Hyo Jeong Kim; Jong Sam Lee; Chang Keun Kim (European Journal of Applied Physiology, 2004)

cDNA cloning and mRNA expression of LIM protein gene homologue from the silkworm, Bombyx mori - Jae-Sam Hwang; Hyun-Jeong Go; Tae-Won Goo; Eun-Young Yun; Kwang-Ho Choi; Su-Il Seong; Jong-Su Chang; Sang-Mong Lee; Bong-Hee Lee; Ik-Soo Kim; Nam Soon Kim; Taehoon Chun; et al. (Biotechnology Letters, 2004)

Short-term Changes of Community Structure of Phytoplankton in Summer Around Namhae Island of Korea - Wol Ae Im; Chang Geun Gang; Suk Yang Kim; Sam Geun Lee; Hak Gyun Kim; Ik Gyo Jeong (Algae, 2003)

Induction of pepper cDNA encoding a lipid transfer protein during the resistance response to tobacco mosaic virus - Chang-Jin Park; Ryoung Shin; Jeong Mee Park; Gil-Je Lee; Jin-Sam You; Kyung-Hee Paek (Plant Molecular Biology, 2002)

Prostate-specific Membrane Antigen (PSMA)-specific Monoclonal Antibodies in the Treatment of Prostate and Other Cancers - Michael C. Gong; Sam S. Chang; Michel Sadelain; Neil H. Bander; Warren D.W. Heston (Cancer and Metastasis Reviews, 1999)